Deciphering aquaporin-4’s influence on perivascular diffusion indices using DTI in rat stroke studies - Jiaqi Tian; Jiaqi Tian; Yuwen Zhang; Le Liu; Chaofan Li; Xiaozhu Hao (Frontiers in Neuroscience)
BackgroundThis study aimed to evaluate the dynamic changes of the perivascular space diffusion index (index for diffusivity along the perivascular space, ALPS) and its relationship with aquaporin 4 (AQP4) polarization after cerebral ischemia in rats.MethodsRats were subjected to transient middle cerebral artery occlusion (tMCAO) and evaluated at 1, 3, 7, 14, and 28 days post-ischemia using diffusion tensor imaging (DTI), T2-weighted imaging (T2WI), and susceptibility-weighted imaging (SWI). The ALPS index was determined from imaging data, focusing on periventricular and corpus callosum/cingulate regions. Brains were analyzed for AQP4 and glial fibrillary acidic protein (GFAP) via immunofluorescence.ResultsThe results showed that ischemic rats displayed reduced ALPS indexes, particularly on the ipsilateral side, with an initial decrease at day 1 and subsequent recovery by days 14 and 28. AQP4 polarization in the non-glial scar area around the infarction followed a similar pattern, demonstrating that there was a concordant trend between the ALPS index and AQP4 polarization status.ConclusionIn conclusion, the ALPS index can reflect changes in AQP4-mediated glymphatic pathway function, suggesting a significant decline in the hyperacute phase and a notable recovery in the early chronic phase, which may have implications for stroke therapeutic strategies.